Optimization of Cassava Starch/Onion Peel Powder-Based Bioplastics: Influence of Composition on Mechanical Properties and Biodegradability Using Central Composite Design - Assala Torche; Chouana Toufik; Fairouz Djeghim; Ibtissem Sanah; Rabah Arhab; Maria D’Elia; Luca Rastrelli (Foods)
Synthetic plastic pollution represents a major global concern, driving the search for sustainable and biodegradable packaging alternatives. However, many biodegradable plastics suffer from inadequate mechanical performance. This study aimed to develop a biodegradable film based on cassava starch, incorporating onion peel powder (OPP), a byproduct rich in quercetin derivatives, as a reinforcing agent and plasticized with crude glycerol. A Central Composite Design (CCD), implemented using Minitab 19, was employed to investigate the effects of starch (60–80%) and OPP (0–40%) content on the mechanical properties and biodegradability of the resulting bioplastics. Three optimized formulations were identified according to specific performance criteria. The first formulation, containing 72.07% starch and 21.06% OPP, was optimized for maximum tensile strength while maintaining target values for elongation and biodegradability. The second, composed of 77.28% starch and 37.69% OPP, was optimized to enhance tensile strength and biodegradability while minimizing elongation. The third formulation, with 84.56% starch and 27.74% OPP, aimed to achieve a balanced optimization of tensile strength, elongation, and biodegradability. After a 30-day soil burial test, these formulations exhibited weight loss percentages of 31.86%, 29.12%, and 29.02%, respectively, confirming their biodegradability. This study optimized the mechanical and biodegradability properties of cassava starch-based bioplastics using statistical modeling. The optimized formulations show potential for application in sustainable food packaging.